In vivo toxicity study of aqueous extracts of cymbopogon citratus (Lemongrass) - Maetalong, Majid; Darnis, Deny Susanti; Zamli, Zaitunnatakhin; Ramli, Norazsida (2014)
Aqueous extraction was done by carefully selecting, washing, chopping and blending of 2 kg of C. citratus in 1 L of distilled water. The mixture was then simmered in a 50 °C water bath for an hour, finely filtered, frozen in a -80 °C freezer and then freeze dried. The 20 mice used were divided into two groups, control and experimental groups with equal sex ratio in each group. The experimental mice were orally administered with a single dose of 5000 mg/kg of C. citratus extracts. Behavioral observation was done for 14 days then all mice were sacrificed. Body weight measurements were taken before and after the 14 days, as well the weights of livers, kidneys and spleens of all mice were also taken after sacrifice. Histopathology examination was performed on all collected organs. Behavioural observation showed in the first hour an initial reduction in the locomotor activity, tachypnea, perioral and general tremor and piloerection. By the 3rd hour, emaciation was noticed, but with less stress and few sings of diarrhoea. The 4th hour showed signs of improvement and increased activity. The subsequent daily observation for 14 days showed no apparent signs of toxicity with a return of normal behaviour. Body weight comparison showed a slight increase in the mean weight of experimental mice, with no significance in the organ weight variation, or the sex as factor. Histopathology sections of the experimental mice have showed mild signs of toxicity, like pyknotic cells, colour variation due to inflammation, swelling and disrupted cells architecture.